Monoallelic Expression of Olfactory Receptors - Monahan, Kevin (Annu Rev Cell Dev Biol, 2015)
The sense of smell collects vital information about the environment by detecting a multitude of chemical odorants. Breadth and sensitivity are provided by a huge number of chemosensory receptor proteins, including more than 1,400 olfactory receptors (ORs). Organizing the sensory information generated by these receptors so that it can be processed and evaluated by the central nervous system is a major challenge. This challenge is overcome by monogenic and monoallelic expression of OR genes. The single OR expressed by each olfactory sensory neuron determines the neuron’s odor sensitivity and the axonal connections it will make to downstream neurons in the olfactory bulb. The expression of a single OR per neuron is accomplished by coupling a slow chromatin-mediated activation process to a fast negative-feedback signal that prevents activation of additional ORs. Singular OR activation is likely orchestrated by a network of interchromosomal enhancer interactions and large-scale changes in nuclear architecture.